‘Guardians of the nation or unruly disciples?’: a critique of youth participation in post-colonial Zimbabwe’s contested political spaces - Mashingaidze, Terence M. (Institute for Security Studies, 2016)
Unbridled desire to monopolise political space compels some ruling African parties to resort to violence, retributive justice and exclusionary discourses in order to neutralise other contenders for state power. Lacking benefi ts of state-controlled propaganda machinery and ‘arms of coercion’ such as the police, the military and the intelligence services, opposition parties respond to some of the ruling parties’ excesses with violence as well. Under such circumstances, the youth are ‘caught in the middle’. Most ruling and opposition political parties have reduced the youth to convenient ‘social instruments’ for repression and indoctrination of citizens. Using Zimbabwe as a case study, this paper explores the roles and terms of youth participation in post-colonial politics. To varying degrees, youth on both sides of Zimbabwe’s political divide have destroyed property, and violated freedoms of assembly, expression and association. Th ey have been the most visible perpetrators of inter- and intra-party violence. Although youth involvement in Zimbabwean politics has been at the instigation of adult political entrepreneurs and social manipulators, other youth have charted an ‘independent political course’ aimed at promoting good governance and fair political practices.